2014
DOI: 10.1103/physrevb.90.045309
|View full text |Cite
|
Sign up to set email alerts
|

Topological phase transition in a topological crystalline insulator induced by finite-size effects

Abstract: We study electronic states and topological invariants of (001)-films of topological crystalline insulator (TCI) PbxSn1−xTe. Gapless surface Dirac cones on bulk TCIs become gapped in thin films due to finite-size effect, which is hybridization between those on the top and bottom surfaces. We clarify that the TCI film has the strong finite-size effect as compared to three-dimensional topological insulators such as Bi2Se3. Moreover, the energy gap oscillates with the thickness of film. The oscillation stems from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 65 publications
10
48
1
Order By: Relevance
“…In addition, in the normal state, it has been revealed that the edge state of (001) film dramatically changes depending on the number of layers [82]. It can be expected that the similar situation may occur in the superconducting state due to the existence of the steps on the surface.…”
Section: Interpretation Of Experiments and Discussionmentioning
confidence: 88%
“…In addition, in the normal state, it has been revealed that the edge state of (001) film dramatically changes depending on the number of layers [82]. It can be expected that the similar situation may occur in the superconducting state due to the existence of the steps on the surface.…”
Section: Interpretation Of Experiments and Discussionmentioning
confidence: 88%
“…There are many proposed TCI phases depending on different crystal symmetries [4][5][6][7][8][9], yet those relying on mirror symmetry [10] are of particular interest as they have been experimentally observed in, for example, IV-VI semiconductors SnTe, Pb 1−x Sn x Te, and Pb 1−x Sn x Se [11][12][13][14][15]. More materials are theoretically proposed to realize the TCI phases such as rocksalt semiconductors [16,17], pyrochlore iridates [18], graphene systems [19], heavy fermion compounds [20,21], and antiperovskites [22], including two-dimensional (2D) materials such as SnTe thin films [23,24] and a (001) monolayer of PbSe [25].…”
mentioning
confidence: 99%
“…Due to the cubic structure in the bulk, electronic structures of IV-VI semiconductor thin films depend crucially on the growth direction [19][20][21][22] . In this work, we study (111) thin films of IV-VI TCIs, which have been grown epitaxially in recent experiments 11,15 .…”
mentioning
confidence: 99%